Challenges in the Management of Pediatric Pancreatic Hydatid Disease: A Systematic Review of the Literature and Our Clinical Experience - Suresh Kumar Thanneeru; K. Priyesh Sankar; Pramod K. Sharma; Roshan Chanchlani; Vishal Gupta; Erukkambattu Jayashankar; Amit Agrawal (Journal of Indian Association of Pediatric Surgeons)
Pancreatic hydatid disease (PHD) in children is rare compared to liver and lung involvement. The rarity and overlap with other cystic lesions often lead to challenges in the preoperative diagnosis and intraoperative surprises. Clear guidelines on the appropriate management of PHD are lacking. This review is intended to address these gaps in the literature. A systematic literature search was performed in PubMed, Scopus, Cochrane Central Registry of Controlled Trials (The Cochrane Library), and ScienceDirect databases for pediatric PHD. Observational studies such as case reports, case series, and retrospective studies were included. Letters, editorials, conference abstracts, comments, animal studies, and non-English literature studies were excluded. After sorting out 794 articles, 11 articles describing 16 patients (including our cases) were included in qualitative synthesis. The author’s two cases were described separately. Preoperative diagnosis was made in only 35.71% of the patients. Both the conservative surgical (92.86%) and radical approaches (7.14%) have been described with favorable results (85.71%). One patient managed with the conservative surgical approach developed a pancreatic leak. No recurrence was reported. PHD in children is rare. Accurate preoperative diagnosis is uncommon and requires a high index of suspicion. A normal pancreas, nondilated pancreatic duct, and normal enzymes in a patient from an endemic zone should prompt consideration of PHD. Surgical management must be individualized due to the limited data. Both conservative and radical approaches can be effective, but caution is needed for potential pancreatic leaks after the conservative approach due to ductal communication.